Synthesis and characterization of CoCrFeNi1.75-xTi0.25+x high entropy alloy. (2022) - Chand, Suresh; Kumar Rana, Navjeevan; Rakha, Khushboo; Reza, Shahriar; Batra, Uma
Abstract: High entropy alloys are part of a novel area of metallurgy concerning alloys containing at least five elements with an atomic percentage ranging from 5 at% to 35 at%. The interest arises as for plenty of compositions, the formation of simple solid solutions gives rise to promising properties, pertaining their use in different fields such as structural, nuclear, automotive and aerospace industries. The main objective of this study was to synthesize CoCrFeNi1.75-x Ti0.25+x (x = 0, 0.05, 0.15, 0.25) non-equiatomic, single-phase, high entropy alloys (HEAs) based on the multi-component Co-Cr-Fe-Ni-Ti system were produced by melting route in vacuum arc furnace. The characterization of newly developed HEAs was carried out using X-Ray Diffraction (XRD) and Optical Microscopy. XRD and optical microscopy confirmed the formation of single phase Ni(CoCrFeTi) FCC alloys system and dendritic structure respectively. Electrochemical workstation was used to test the corrosion behaviour of newly developed High entropy alloys in 3.5 wt% NaCl and 0.5 M H2 SO4 aqueous solution at room temperature. The corrosion current density (Icorr ) of the alloys decreased with the increase of Ti content. When the Ti content increased from 5 at% to 10 at% the value of (Icorr ) decreased from 0.423μA to 0.270 μA in 3.5 wt% NaCl and from 21.42 μA to 16.84 μA in 0.5 M H2 SO4 aqueous solution respectively.